PENINGKATAN PRESTASI BELAJAR IPS MELALUI MODEL PEMBELAJARAN PAIKEM PADA SISWA KELAS IX-A SMPN 2 GUNUNG BINTANG AWAI - SRIWATIE, VIVIT (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2023)
The implementation of this Classroom Action Research aims to improve the learning outcomes of class IX-A students at SMPN 2 Gunung Bintang Awai in social studies learning. This PTK consists of 2 cycles, with each cycle containing planning, action, observation and reflection stages. The action objects studied include learning outcomes and the completeness of student learning outcomes in each cycle. The research subjects were 19 students in class IX-A of SMPN 2 Gunung Bintang Awai, consisting of 11 men and 8 women. In this study, the data collected were student learning outcomes, both the grades obtained by students and the percentage of classical completion. Learning outcome data is obtained by conducting a learning outcomes test, with written test questions in the form of descriptions. The results of this research show a significant increase in student activity and student learning outcomes. The increase in student activity is shown by an increase in the number of active students and the learning process in each cycle. Meanwhile, the increase in student learning achievement was proven by an increase in the average class score, namely cycle I 72.21, cycle II 77.72 and cycle II 82.46. And the number of students who reached the KKM and completed their studies was 76.79% in cycle I, increased to 83.93% in cycle II and increased again to 92.86% in cycle III. Thus, student learning outcomes have been achieved classically. ABSTRAKPelaksanaan Penelitian Tindakan Kelas ini bertujuan untuk meningkatkan hasil belajar siswa kelas IX-A SMPN 2 Gunung Bintang Awai dalam pembelajarn IPS. PTK ini terdiri dari 2 siklus, dengan tiap-tiap siklus memuat tahap perencanaan,tindakan, observasi,dan refleksi. Objek tidakan yang diteliti meliputi hasil belajar dan ketuntasan hasil belajar siswa pada tiap-tiap siklus. Subjek Penelitian adalah siswa kelas IX-A SMPN 2 Gunung Bintang Awai yang berjumlah 19 Orang, terdiri dari 11 Laki-laki dan 8 Perempuan. Dalam penelitian ini data yang dikumpulkan adalah hasil belajar siswa baik nilai yang diperoleh siswa maupun presentase ketuntasan secara klasikal. Data hasil belajar diperoleh dengan melakukan tes hasil belajar, dengan soal tes tertulis berbentuk uraian. Hasil Penelitian ini menunjukkan terjadinya peningkatan yang signifikan pada keaktifan siswa maupun nilai hasil belajar siswa. Peningkatan keaktifan siswa ditunjukkan dengan terjadinya peningkatan jumlah siswa yang aktif dan proses pembelajaran pada tiap-tiap siklus. Sedangkan peningkatan prestasi belajar siswa dibuktikan dengan terjadinya peningkatan nilai rata-ratakelas yaitu siklus I 72,21, siklus II 77,72 dan siklus II 82,46. Dan jumlah siswa yang mencapai KKM dan tuntas belajar adalah 76,79% pada siklus I, meningkat menjadi 83,93% pada siklus II dan meningkat lagi menjadi 92,86% pada siklus III. Dengan demikian hasil belajar siswa telah mencapai secara kalsikal.